(untitled) (Global Journal of Cultural Studies, 2023)
To analyze the depiction of sacred space and rituals in Paulo Coelho’s The Pilgrimage is the purpose of this essay. The bulk of studies on the functions and aims of pilgrimage have produced a multifaceted field of research for the further development of both secular and religious conceptualizations of this ritualized behavior. Whether pilgrimage is a matter of ideology, union with the sacred space, spiritual enlightenment, superstition, political identity, primitive religiosity, post-mortem body, or simply a matter of our attitudes toward pilgrimage as outsiders or insiders is still unresolved. In this article, I review the significance and purpose of pilgrimage in its traditional and anthropological context and in regard to the importance of sacred space or destination in various religions. Next, I approach the tradition of pilgrimage in the novel by drawing upon Gilles Deleuze’s critique of being, becoming, and animal. I subsequently explore three principal intersections that the protagonist experiences in his spiritual journey to the holy space, the cathedral of Santiago de Compostela in Spain. I discuss how The Pilgrimage presents a non-traditional portrayal of sacred space and pilgrimage. I also explore the reciprocity between the pilgrim’s body and mind in developing a physical and mental relation with his natural environment. Whereas man’s desire for the divine or holy space has received considerable attention in the studies on pilgrimage, Coelho’s novel reorients the focus of attention from the final destination to the pilgrim’s modes of symbiosis along the road. This article also intends to demonstrate how the novel presents a new perspective for the study of the ritual, recognized as pilgrimage.